2018
DOI: 10.1002/ecs2.2205
|View full text |Cite
|
Sign up to set email alerts
|

High interspecific variation in nutrient excretion within a guild of closely related caddisfly species

Abstract: Abstract. Understanding the amount of variation in functional traits between closely related species within guilds is critical for understanding links between community composition and ecosystem processes. Nutrient excretion is an important link between animals and their environments, and aquatic invertebrate communities can supply a considerable proportion of ecosystem nutrient demand via excretion. We quantified nitrogen (N) and phosphorus (P) excretion rates of 10 species of larval caddisflies that inhabit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…This lower tissue N:P resulted in higher excretion N:P. We suggest that since tissue stoichiometry, especially N:P, varies as a result of life‐history characteristics, it is a powerful tool for examining the congruence between evolutionary history and trait variation, and their consequential effects of community assembly and ecosystem function. Recent work in ES and consumer‐driven nutrient dynamics has shown a large degree of intra‐ and interspecific variation in tissue and nutrient recycling stoichiometry (El‐Sabaawi et al 2015, Balik et al 2018, Dalton et al 2018) and further research across taxa, populations, and life stages will help elucidate the patterns and processes associated with stoichiometric niche partitioning.…”
Section: Discussionmentioning
confidence: 99%
“…This lower tissue N:P resulted in higher excretion N:P. We suggest that since tissue stoichiometry, especially N:P, varies as a result of life‐history characteristics, it is a powerful tool for examining the congruence between evolutionary history and trait variation, and their consequential effects of community assembly and ecosystem function. Recent work in ES and consumer‐driven nutrient dynamics has shown a large degree of intra‐ and interspecific variation in tissue and nutrient recycling stoichiometry (El‐Sabaawi et al 2015, Balik et al 2018, Dalton et al 2018) and further research across taxa, populations, and life stages will help elucidate the patterns and processes associated with stoichiometric niche partitioning.…”
Section: Discussionmentioning
confidence: 99%
“…Although crayfish stoichiometry may vary during base-flow conditions, we predict that nutrients controlled by crayfishes may be important to ecosystem functions, including microbial respiration and leaf decomposition in isolated pools dominated by this group (Rosemond, Pringle, Ramírex, Paul, & Meyer, 2002). Other aquatic macroinvertebrates not quantified in our study can maintain high densities during stream drying (Boulton & Lake, 1992) and their contributions to nutrient cycling may exceed that of the macroconsumers measured here Balik, Taylor, Washko, & Wissinger, 2018). Regardless, our study contributes evidence that the relative dominance of broad taxonomic groups (e.g.…”
Section: N Demand By Epilithic Biofilms and Macroconsumer Excretionmentioning
confidence: 50%
“…For example, previous work investigating somatic stoichiometry of crayfish (Evans-White & Lamberti, 2005) indicated that they might act as P sinks in isolated pools given their relatively high excretion N:P and low N:P tissue stoichiometry. Other aquatic macroinvertebrates not quantified in our study can maintain high densities during stream drying (Boulton & Lake, 1992) and their contributions to nutrient cycling may exceed that of the macroconsumers measured here Balik, Taylor, Washko, & Wissinger, 2018). Other aquatic macroinvertebrates not quantified in our study can maintain high densities during stream drying (Boulton & Lake, 1992) and their contributions to nutrient cycling may exceed that of the macroconsumers measured here Balik, Taylor, Washko, & Wissinger, 2018).…”
Section: F I G U R Ementioning
confidence: 50%
“…Hydropsychid caddisflies have alternative forms of silk structures depending on several environmental factors, including pollutants, flow velocity, and species (Petersen & Petersen, 1983;Loudon & Alstad, 1992;Balch et al, 2000;Wiggins, 2007;Albertson et al, 2014b). A growing body of literature highlights the importance of both inter-and intraspecific trait variation in modulating animal-environment realtionships (Bolnick et al, 2011;Balik et al, 2018). In our study system, this variation in form and durability of the caddisfly retreat structures could mediate how much a particular retreat influences local flow conditions since evidence does suggest that net-building design is plastic and not under strict genetic control (Plague & McArthur, 2003).…”
Section: Discussionmentioning
confidence: 99%